Multiresolution Analysis Applied to the Monge-Kantorovich Problem - Armando Sánchez-Nungaray; Carlos González-Flores; Raquiel R. López-Martínez (Abstract and Applied Analysis)
We give a scheme of approximation of the MK problem based on the symmetries of the underlying spaces. We take a Haar type MRA constructed according to the geometry of our spaces. Thus, applying the Haar type MRA based on symmetries to the MK problem, we obtain a sequence of transportation problem that approximates the original MK problem for each of MRA. Moreover, the optimal solutions of each level solution converge in the weak sense to the optimal solution of original problem.